Factors Responsible for Marital Infidelity among Ipata Market Women in Ilorin Kwara State - Akorede, Seun Nurudeen; Usman, Mahammed Danlami; Nofiu, Oluwatobi Daniel; Ibrahim, Babangida Umar (NIU Journal of Social Sciences, 2018)
Marital infidelity also known as extra marital affairs is one of the commonly pronounced problem in marriage, it also include extra marital relationship, cheating and sexual intercourse. Moderating variables like family type, age, employability status and religion were considered as factors responsible for marital infidelity as perceived by women. This study investigated factors responsible for marital infidelity among Ipata market women in Ilorin south local government area, Kwara State. The descriptive survey method was adopted for the study. A total of 230 women were selected using purposive and simple random sampling techniques. An instrument titled ‘Factors Responsible for Marital Infidelity Questionnaire (FRMQ) was used to obtain data from the respondents. The data generated was analyzed using frequency counts and percentage for the demographic data while Analysis of variance (ANOVA) were used to test the three postulated hypotheses at 0.05 alpha level. The finding revealed that there is no significant difference in factor responsible for marital infidelity as perceived by women in Ilorin south local government area of Kwara State on the basis of family type. Also there is significant difference in factor responsible for marital infidelity as perceived by women in Ilorin south local government area Kwara State on the basis of age, employability status and religion. Based on the findings of the study, it was recommended that counsellors should enlightened couples on needs to engage in satisfactory sexual relationship; in addition counsellors in collaboration with health workers should enlightened couples on how to improve their sexual urge towards each other and overcome frigidity. In order to reduce the risk of marital infidelity among women, it is necessary for woman to engage in one occupation or trade and women should be encouraged not to trade their marital integrity on the platform of job security